An efficient multi-agent negotiation algorithm for multi-period photovoltaic array reconfiguration with a hydrogen energy storage system. (15th March 2022) - Zhang, Xiaoshun; Yu, Tao; Ma, Xiaoguang; Guo, Lexin
Highlights: A new multi-period photovoltaic array reconfiguration is constructed. The photovoltaic array is coordinated with a hydrogen energy storage system. The regulation cost and hydrogen selling profit from other markets are introduced. A novel distributed algorithm named efficient multi-agent negotiation is proposed. The total profit of photovoltaic system is raised under partial shading conditions. Abstract: Since the partial shading conditions easily bring a significant energy loss for a photovoltaic system, various array reconfiguration techniques have been proposed to improve the power generation efficiency. The existing studies of photovoltaic array reconfiguration mainly attempted to maximize the power output, which easily leads to a low total profit since they did not take the multi-period power fluctuation into account. In general, a large power fluctuation will result in a high regulation cost in a frequency regulation market, which can be smoothed by a hydrogen energy storage system. Consequently, this paper constructs a new multi-period photovoltaic array reconfiguration with a hydrogen energy storage system under partial shading conditions. It aims to maximize the total profit of photovoltaic system instead of only the power output by simultaneously consider the electricity selling profit in an electricity market, the hydrogen selling profit in a hydrogen market, and the regulation cost in a frequency regulation market. To address this problem, a novel efficient multi-agent negotiation algorithm with an auctioneer and multiple bidders is designed with the multi-round negotiation and the random re-initialization. The comprehensive case studies with a 10 × 10 total-cross-tied photovoltaic array shows that the proposed algorithm can acquire the higher total profit compared to five centralized meta -heuristic algorithms, in which the total profit can be increased from negative to positive against that without optimization under a discrete varying partial shading condition. Based on the simulation results, it can be concluded that the multi-period photovoltaic array reconfiguration can dramatically increase the total profit under a multi-market environment, while the proposed algorithm can achieve an efficient and distributed optimization under different partial shading conditions.